Pengaruh Model Pembelajaran Inkuiri dan Kooperatif Terhadap Kemampuan Kognitif Siswa pada Materi Animalia di SMA Negeri 11 Medan - Hutri Purnama Sari Lubis; Ely Djulia; Syahmi Edi (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
The Effect of Inquiry and Cooperative Learning Model On Students Cognitive Skills in Animalia Topic in SMA Negeri 11 Medan. A Thesis. Medan: Postgraduate Program State University of Medan, 2016.This research aims to determine the effect of the learning model on: (1) Students Cognitive Skills in SMA Negeri 11 Medan. The research applied experimental queasy method research with 3 classes which were choosing by using cluster random sampling technique. The class X7 learn with inquiry learning model, class X8 with cooperative (Group Investigation) learning model, and while class X9 (control) with conventional learning model. The research instrument were the test of cognitive skills in essay test. The data analysis technique used Covariat Analysis at the level of significance α = 0.005 by using SPSS 21.0. The results showed that: (1) there was significant effect of learning model on students’ cognitive skills (F= 15.916; P= 0.000). The cognitive skills learn by inquiry learning model (87.46±5.404) is significant higher than cooperative (Group Investigation) learning model (83.13 ± 6.509), and conventional learning model (79.73±6.329). The study imply that expected to the teachers to be able to conduct inquiry and cooperative (Group Investigation) learning in Animalia topic as the effort to improve the cognitive skills.